Assessment of different stress responses after laparoscopic and open cholecystectomy in patients attending tertiary care hospital, Bhuj, Gujarat, India: a prospective study - Kothari, Bhavin; Rao, Gyaneshwar (International Surgery Journal, 2017)
Background: Surgical trauma by incision and dissection of tissue stimulates the body to respond proportionately to the extent of injury. This study was conducted with an aim to compare metabolic and inflammatory responses after laparoscopic and open cholecystectomy namely serum cortisol and C-reactive protein levels before and after operation at Bhuj, Kutch, India. Methods: Present study was non-randomized, and comparative study carry out in the General Surgery Department at Gujarat Adani prospective institute of Medical Science, Bhuj, Kutch, Gujarat, India for an era of two years. One hundred and two patients were included in this study and were divided into two groups of open and laparoscopic cholecystectomy. Out of these 102 patients, 41 undergo open cholecystectomy and 61 laparoscopic cholecystectomy. Preoperative, intraoperative, postoperative and anesthetic medications were consistent in all the patients. Results: It was found that metabolic responses like serum cortisol were significantly higher after open procedure 6 hours and 48 hours postoperatively. Similarly, inflammatory response indicator C-reactive protein was raised significantly higher 48 hours after open as compared to laparoscopic cholecystectomy. Conclusions: Open cholecystectomy caused further tissue responses as compared to its laparoscopic alternative.